Involvement of High-Conductance Calcium-Dependent Potassium Channels in Short-Term Presynaptic Plasticity in the Rat Dentate Gyrus - Baluchnejadmojarad, T.; Roghani, M. (Нейрофизиология, 2013)
We examined the involvement of high-conductance calcium-dependent potassium (BK) channels in short-term presynaptic plasticity in the rat dentate gyrus; a paired-pulse stimulation
protocol was used for evaluation of this phenomenon. Paired-pulse responses were recorded
from the dentate gyrus of rats while stimulating the medial part of the perforant path with
different interpulse intervals (IPIs). Iberiotoxin (IbTX), a selective blocker of BK channels,
at doses of 50 and 100 mg/kg was i.p. administered 30 min presurgery. The population spike
(PS) amplitude ratio and field EPSP (fEPSP) amplitude and slope ratios were measured at
IPIs 10, 20, 30, and 50 msec as indices of synaptic facilitation and/or depression. At IPIs of
10 and 20 msec, there was no significant increase in the PS amplitude ratio after IbTX. However, at longer IPIs (30 and 50 msec), there was a significant dose-dependent increase in this
ratio vs the vehicle group (P < 0.05 and P < 0.01, respectively). There was a slight decrease
in the fEPSP amplitude ratio at short IPIs (10, 20, and 30 msec) in rats pretreated with IbTX,
while insignificant incrases in the fEPSP amplitude ratio were observed at longer IPIs (50
msec). With respect to the fEPSP slope ratio, IbTX dose-dependently and insignificantly
increased it. In addition, longer IPIs did not provide significant changes in the fEPSP slope
ratio. High-conductance calcium-dependent potassium channels in the rat dentate gyrus have
a modulatory (inhibitory) and (apparently) regulatory role in short-term presynaptic plasticity at relatively long ISIs, and blocking of these channels leads to paired-pulse facilitation. Ми досліджували залучення викосопровідних кальційзалежних калієвих каналів (BK-каналів) у короткочасну пресинаптичну пластичність у зубчастій звивині щурів; для
оцінки цього феномену застосовували протокол парної стимуляції. Відповіді у зубчастій звивині реєстрували після
подразнення медіальної частини перфорантного шляху парними стимулами, що подавалися з різними міжстимульними інтервалами (МСІ). Іберіотоксин (IbTX) – селективний
блокатор BK-каналів – ін’єкували внутрішньоочеревинно
в дозах 50 та 100 мкг/кг за 30 хв до початку відведення.
Відношення амплітуд популяційних піків (ПП), амплітуд
популяційних викликаних постсинаптичних потенціалів
(пВПСП) і значень швидкості наростання останніх вимірювали при МСІ, що дорівнювали 10, 20, 30 та 50 мс; ці величини розглядали як індекси синаптичного полегшення або
депресії. Після введення IbTX у випадках, коли МСІ становили 10 та 20 мс, ми не спостерігали значного зростання
відношення амплітуд ПП. Проте у випадках, коли використовували триваліші МСІ (30 та 50 мс), цей індекс демонстрував значне дозозалежне збільшення (порівняно з його
значеннями в групі щурів, які отримували розчинник. Щодо
відношення амплітуд пВПСП слід зазначити, що ми спостерігали слабке зменшення даного індексу у тварин, котрим
попередньо ін’єкували IbTX, у випадках використання коротких МСІ (10, 20 та 30 мс) і незначне збільшення такого
відношення при триваліших МСІ (50 мс). Що ж до швидкості наростання пВПСП, то IbTX дозозалежно та статистично невірогідно збільшував вказаний індекс. Крім того,
збільшення тривалості МСІ не спричиняло значних змін
швидкості наростання цих потенціалів. У межах зубчастої
звивини щурів BK-канали відіграють модуляторну (гальмівну) та, безсумнівно, регуляторну роль у короткотривалій
пресинаптичній пластичності при відносно тривалих МСІ;
блокування даних каналів призводить до полегшення в умовах парної стимуляції.